Digitalization, organizational change, and human resource management at the Immigration Polytechnic - Akbar, Rasona Sunara; Abdurahman, Ayi; Nursanto, Gunawan Ari; Hartati, Besse (Goodwood Publishing, 2025)
Purpose: This study aims to examine how digitalization influences and is influenced by organizational structures and human resource management in the Indonesian education industry. Research Methodology: This study employs a qualitative approach using semi-structured interviews and focused group discussions to explore how digital technology is implemented in human resource management within the Indonesian education sector. Participants include education leaders, HR officials, policymakers, and edutech developers, selected through purposive and snowball sampling methods to ensure relevant and in-depth insights. Data were collected through individual interviews and thematic workshops, allowing researchers to capture both personal experiences and group dynamics related to digital transformation challenges and strategies. Results: The results show that the success of digital transformation in HR management in Indonesia's education sector depends on the balance between human, technological and organizational aspects. Key challenges include a lack of training, uneven infrastructure, and an organizational culture that is not adaptive to change. Therefore, a holistic strategy is needed that includes digital competency development, visionary leadership, and policies that support technological innovation and transparency. Conclusions: Digital transformation in HRM within Indonesia's education sector is hindered by gaps in human skills, technology access, and rigid organizational structures. Weak digital leadership and ethical concerns around AI further slow progress. A holistic approach developing digital competencies, promoting innovation, and ensuring transparent AI is essential for effective and sustainable transformation. Limitations: The study’s qualitative scope limits generalizability. It also reflects a specific time frame and may include selection bias from purposive sampling. Contribution: This study offers insights into aligning HR and digital strategies using the HTO framework and promotes ethical, inclusive digital transformation in education.